Constitutionally Conforming Interpretation in Canada - Daly, Paul (Constitutionally Conforming Interpretation – Comparative Perspectives: Volume 1: National Reports, 2023)
This is the first part of a 2-volume set that presents an in-depth investigation into the canon of constitutionally conforming interpretation. These volumes address the fundamental issues the canon raises in the national, supranational and international contexts. In volume 1, experts from 19 jurisdictions, including Brazil, Canada, India, the UK, and the USA, present reports which give concise overviews of the approaches and debates on constitutionally conforming interpretation. These reports cover the structural background, the conditions of application, as well as issues of competence. Further aspects discussed are its perceived normativity and popularity in everyday legal practice. Together with volume 2, which explores the canon’s use and theoretical impact beyond the national context in a comparative and critical manner, this book fills an important gap in legal scholarship and sets the stage for cross-national discourse.